2016
DOI: 10.1016/j.exger.2016.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Gene-diet interactions and aging in C. elegans

Abstract: Diet is the most variable aspect of life history, as most individuals have a large diversity of food choices, varying in the type and amount that they ingest. In the short-term, diet can affect metabolism and energy levels. However, in the long run, the net deficiency or excess of calories from diet can influence the progression and severity of age-related diseases. An old and yet still debated question is: how do specific dietary choices impact health- and lifespan? It is clear that genetics can play a critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 140 publications
(193 reference statements)
1
35
0
Order By: Relevance
“…For example, studies exploiting Mendelian randomization have not shown a compelling causal link between triglyceride levels on longevity in humans (Liu et al, 2017). In general, a diet high in fat leads to obesity and reduced lifespan in diverse species including Drosophila, C. elegans and mice (Otabe et al, 2007), (Yen and Curran, 2016), (Gáliková and Klepsatel, 2018). However, consumption of high levels of corn oil rich in poly-and monounsaturated fats (58.6% fat-derived calories) in C57BL/6 male mice has been shown to improve health and longevity, provided that total calorie consumption stays within normal bounds (Si et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies exploiting Mendelian randomization have not shown a compelling causal link between triglyceride levels on longevity in humans (Liu et al, 2017). In general, a diet high in fat leads to obesity and reduced lifespan in diverse species including Drosophila, C. elegans and mice (Otabe et al, 2007), (Yen and Curran, 2016), (Gáliková and Klepsatel, 2018). However, consumption of high levels of corn oil rich in poly-and monounsaturated fats (58.6% fat-derived calories) in C57BL/6 male mice has been shown to improve health and longevity, provided that total calorie consumption stays within normal bounds (Si et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the discrepancies between sex, or strain variations in sensing and handling of substrates, may convolute the interpretation of data derived from animal model systems ( 304 ). Differences in experimental approaches and the techniques used to measure metabolic flexibility may influence outcomes ( 305 ). Methodological differences can severely impact interpretation of study data ( 106 ), advocating for a gold-standard application of available methods and technology.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In recent years, a growing body of research on dietary restriction, food choice, nutrient intake, and gene‐diet interactions has been conducted in C. elegans , demonstrating among other things how diet can have long‐lasting effects on animal physiology and even influence future generations (reviewed in ref. ). In this context, the current study aimed to address the question if supplementation with Se species in an early life stage has long‐term protective effects after supplementation is ceased.…”
Section: Introductionmentioning
confidence: 97%
“…The alternative and complementary in vivo model C. elegans is commonly used in mechanistic studies in toxicological, biomedical, and aging research, due to its rapid life cycle, genetic manipulability, and high degree of evolutionary conserved genes and pathways . Many core metabolic pathways are conserved between humans and C. elegans , including the insulin/IGF‐1, AMPK, and TOR pathways, as well as transcription factors and nuclear hormone receptors involved in lipid and energy homeostasis . In addition to being a well‐established model for neurodegenerative diseases, C. elegans applications to study metabolic disorders, such as diabetes or obesity are available as well (summarized in refs.…”
Section: Introductionmentioning
confidence: 99%